Magnetic Particle Imaging–Guided Stenting. (August 2019) - Herz, Stefan; Vogel, Patrick; Kampf, Thomas; Dietrich, Philipp; Veldhoen, Simon; Rückert, Martin A.; Kickuth, Ralph; Behr, Volker C.; Bley, Thorsten A.
Purpose: To assess the feasibility of magnetic particle imaging (MPI) to guide stenting in a phantom model.Materials and Methods: MPI is a new tomographic imaging method based on the background-free magnetic field detection of a tracer agent composed of superparamagnetic iron oxide nanoparticles (SPIOs). All experiments were conducted on a custom-built MPI scanner (field of view: 29-mm diameter, 65-mm length; isotropic spatial resolution 1–1.5-mm). Stenosis phantoms (n=3) consisted of polyvinyl chloride (PVC) tubes (8-mm inner diameter) prepared with centrally aligned cable binders to form a ~50% stenosis. A dedicated image reconstruction algorithm allowed precise tracking of endovascular instruments at 8 frames/s with a latency time of ~115 ms. A custom-made MPI-visible lacquer was used to manually label conventional guidewires, balloon catheters, and stainless steel balloon-expandable stents. Vascular stenoses were visualized by injecting a diluted SPIO tracer (ferucarbotran, 10 mmol iron/L) into the vessel phantoms. Balloon angioplasty and stent placement were performed by inflating balloon catheters and stent delivery balloons with diluted ferucarbotran.Results: After deployment of the stent, the markers on its ends were clearly visible. The applied lacquer markers were thin enough to not relevantly alter gliding properties of the devices while withstanding friction during the experiments. Placing an optimized flexible lacquer formulation on the preexisting radiopaque stent markers provided enough stability to withstand stent expansion. Final MPA confirmed successful stenosis treatment, facilitated by the disappearance of the lacquer markers on the stent due to differences in SPIO concentration. Thus, the in-stent lumen could be visualized without interference by the signal from the markers.Conclusion: Near real-time visualization of MPI-guided stenting of stenoses in a phantom model is feasible. Optimized MPI-visible markers can withstand the expansion process of stents.